Nanoscale Mesoscopic Structural States in Low-Alloy Steels for Martensitic Phase Formation and Low-Temperature Toughness Enhancement; Physical Mesomechanics; Vol. 23, iss. 5 - Panin V. E. Viktor Evgenyevich; Shulepov I. A. Ivan Anisimovich; Derevyagina L. S. Lyudmila Sergeevna; Panin S. V. Sergey Viktorovich; Gordienko A. I. Antonina Ildarovna; Vlasov I. V. Ilya Viktorovich (2020, 2020)
Title screen